Effect of the quick strength and aerobic endurance trainings on amateur footbaeer’s blood lipids - Savucu, Yüksel; Hamzaoğulları, A. Kerim; Özaltaş, Hüseyin N.; Devecioğlu, Sebahattin; Coşkuner, Zeki; Arslan, Cengiz (My University, 2011)
Football training is affected by many factors using scientific methods in terms of performance. We aimed to search the impact of quick strength and aerobic endurance trainings on forty male amateur footballer’s some blood lipid parameters. Before the new season, first measurements were done by taking their bloods. Then quick strength training was applied a day in a week and other a day aerobics endurance training was applied to 40 footballers (mean=20.88 :£ 2.68 years) with regular football training for 5 months. At the end of regular trainings for five months, second measurements were done by taking their blood samples to compare with the impacts of quick strength and aerobics endurance training on male amateur footballer’s blood lipid profile. The statistical software package program was used to evaluation of statically analyses and received their modifications in the pre-test and post-test comparison of paired Student's I test in level of p<0. 01 . Data are summarized by calculating the average standard deviation, I and p values. As a result, it had been shown that quick strength and aerobics endurance trainings for 20 weeks change footballer’s blood lipid profiles and body compositions positively.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Football; Training; Quick strength; Aerobic endurance; Blood lipids